2016
DOI: 10.1369/0022155416665098
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 20 Co-expression With Dentin Sialophosphoprotein in Human and Monkey Kidneys

Abstract: We recently reported the expression of matrix metalloproteinase 20 (MMP20), hitherto thought to be tooth specific, in the metabolically active ductal epithelial cells of human salivary glands. Furthermore, our report indicated that MMP20 co-expressed and potentially interacts with dentin sialophosphoprotein (DSPP), a member of the small integrin-binding ligand N-linked glycoproteins (SIBLINGs). Our earlier reports have shown the co-expression of three MMPs, MMP2, MMP3, and MMP9, with specific members of the SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…[22][23][24] Published results from our laboratory show SIBLINGs with known MMP partners coexpressing and colocalizing with their cognate MMP partners in highly metabolic duct epithelial systems of the salivary gland and nephron, and in OSCC cells (DSPP-MMP20 in Figure 3E). …”
Section: Siblings As Activators Of Mmpsmentioning
confidence: 84%
See 2 more Smart Citations
“…[22][23][24] Published results from our laboratory show SIBLINGs with known MMP partners coexpressing and colocalizing with their cognate MMP partners in highly metabolic duct epithelial systems of the salivary gland and nephron, and in OSCC cells (DSPP-MMP20 in Figure 3E). …”
Section: Siblings As Activators Of Mmpsmentioning
confidence: 84%
“…[18][19][20][21][22] Recently, we reported the expression of MMP20 in oral squamous cell carcinomas (OSCCs) and metabolically active duct epithelial systems of the salivary gland and nephron, indicating that the tissue distribution of MMP20 under physiologic and pathologic conditions may be wider than previously thought. [22][23][24] On the basis of mechanism of regulation, MMPs are classified into three groups: group 1 (MMP1, -3, -7, -9, -12, -19, and -26) contains a TATA box and an activator protein, AP1, which binds to the Fos and Jun family of transcription factors; …”
Section: Mtmmps Include Mmp14 (Mt1-mmp) -15 (Mt2-mmp) -16 (Mt3-mmp)mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that MMP-20, together with dentin sialophosphoprotein, is expressed not only in the ductal epithelial cells of human salivary glands, but it was also found in all sites of the human and monkey nephron exempting the glomeruli, with a high predominance in the proximal and distal tubular cells [283]. The dentin sialoprotein and MMP-20 pairing may actively participate in the restoration and turnover of ECM proteins of the basement membranes in the monkey and human kidney epithelial cells [283].…”
Section: Enamelysin (Mmp-20)mentioning
confidence: 99%
“…The dentin sialoprotein and MMP-20 pairing may actively participate in the restoration and turnover of ECM proteins of the basement membranes in the monkey and human kidney epithelial cells [283]. …”
Section: Enamelysin (Mmp-20)mentioning
confidence: 99%